THE EFFECT OF HEAT TREATMENT ON THE DURABILITY OF BAMBOO Gigantochloa scortechinii - Kamarudin, Norashikin; Sugiyanto, Krisdianto (Secretariat of Forestry Research and Development Agency, 2012)
Bamboo signifies as one of the fastest growing plants and it can be used for various products. Intropical countries such as Indonesia and Malaysia, bamboo is abundantly available at reasonable prices, therefore it is used for numerous purposes. However, as lignocellulosic material, bamboo is susceptible to fungal and insect attacks. Heat treatment is an option to improve bamboos durability. The objective of this study was to improve the durability of bamboo using hot oil palm treatment. A Malaysian grown bamboo species, Buluh Semantan (Gigantochloa scortechinii), as a study material was soaked in hot oil palm for various temperatures and soaking time, before being inoculated with the basidiomycete Coriolus versicolor in an agar block test. The results demonstrated that the longer the heating time, the more improved the durability of bamboo. Altering the temperature in the palm oil treatment produced varying results. Bamboo blocks that heated in hot oil palm at 100Â°C for 60 minutes shows considerably less weight eduction that indicates less fungal attack. Overall, the higher the temperature, the better the durability of bamboo. Please indicates what the meaning of heat treatment in this experiment, it is not clear.